2021
DOI: 10.2147/cmar.s300559
|View full text |Cite
|
Sign up to set email alerts
|

CircTMCO3 Promotes Gastric Cancer Progression by Regulating miR-577/RAB14 Axis

Abstract: Background Growing evidence indicated that circRNAs played major roles in the progression of human cancer. Nevertheless, the molecular mechanism and effects of circTMCO3 in GC are still unclear. Methods First, qRT-PCR was used to evaluate the levels of circTMCO3 from GC tissues, GC cells, normal tissues and gastric epithelial cells. Then, the GC cells were transfected to analyze the proliferation, migration and invasion of GC cells by MTT, colony formation and transwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Moreover, miR-374a-3p may regulate acute kidney injury by targeting TLR4/NF-κB pathway to reduce the rate of apoptosis and the generation of inflammatory cytokines ( 38 ). Most studies suggested that miR-577 and miR-944 are more commonly expressed in cancers, such as ovarian cancer ( 39 ), gastric cancer ( 40 ), and colorectal cancer ( 41 ), and little is known regarding in T2DM. Nevertheless, recent studies have shown that these genes also participate in fasting glucose control in diabetes via activating Akt signaling pathways and increasing insulin secretion ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-374a-3p may regulate acute kidney injury by targeting TLR4/NF-κB pathway to reduce the rate of apoptosis and the generation of inflammatory cytokines ( 38 ). Most studies suggested that miR-577 and miR-944 are more commonly expressed in cancers, such as ovarian cancer ( 39 ), gastric cancer ( 40 ), and colorectal cancer ( 41 ), and little is known regarding in T2DM. Nevertheless, recent studies have shown that these genes also participate in fasting glucose control in diabetes via activating Akt signaling pathways and increasing insulin secretion ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs have been proven to play important roles in the occurrence and development of many diseases, such as cancer and depression(8-10). circRNAs have been found to be present in the blood, saliva, urine and cerebrospinal uid of tumor patients (11,12), and dysregulated circRNAs can act as oncogenes or tumor suppressors and may contribute to the development and progression of various cancers (13)(14)(15). Thus, can be used as a molecular marker for cancer diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bai et al 19 showed that circ_0007334 contributed to tumor cell growth and angiogenesis by mediating the microRNA-557-5p (miR-557)/KLF12 axis in colorectal cancer. CircTMCO3 accelerated the growth and migration of gastric cancer cells by regulating miR-557/RAB14 axis 20 . In PC, it has been revealed that miR-557 represses PC process via targeting the SLC7A11/PI3K/AKT pathway axis 21 .…”
mentioning
confidence: 99%
“…CircTMCO3 accelerated the growth and migration of gastric cancer cells by regulating miR-557/RAB14 axis. 20 In PC, it has been revealed that miR-557 represses PC process via targeting the SLC7A11/PI3K/AKT pathway axis. 21 However, mechanisms mediated by miR-557 in PC are complex and need further investigation.…”
mentioning
confidence: 99%